Enterprise Architecture Patterns Practical Solutions for Recurring IT-Architecture Problems - Perroud, Thierry; Inversini, Reto.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Every enterprise architect faces similar problems when designing and governing the enterprise architecture of a medium to large enterprise. Design patterns are a well-established concept in software engineering, used to define universally applicable solution schemes. By applying this approach to enterprise architectures, recurring problems in the design and implementation of enterprise architectures can be solved over all layers, from the business layer to the application and data layer down to the technology layer. Inversini and Perroud describe patterns at the level of enterprise architecture, which they refer to as Enterprise Architecture Patterns. These patterns are motivated by recurring problems originating from both the business and the underlying application, or from data and technology architectures of an enterprise such as identity and access management or integration needs. The Enterprise Architecture Patterns help in planning the technological and organizational landscape of an enterprise and its information technology, and are easily embedded into frameworks such as TOGAF, Zachman or FEA. This book is aimed at enterprise architects, software architects, project leaders, business consultants and everyone concerned with questions of IT and enterprise architecture and provides them with a comprehensive catalogue of ready-to-use patterns as well as an extensive theoretical framework to define their own new patterns.
Introduction -- Theory -- The Catalogue and the Map -- More About EAP -- Using Patterns -- Symbols and Their Meanings -- Business Patterns -- Support Patterns -- Infrastructure Patterns -- Appendices.
Keywords: Computer science; Management information systems; Software engineering; Application software; Computer Science; Computer Appl. in Administrative Data Processing; Enterprise Architecture; Software Engineering; Management of Computing and Information Systems; Electronic books